(untitled) (Research, Society and Development, 2022)
Experimentation has become a fundamental approach in chemistry teaching, as it provides a better understanding of the content, as well as an improved view of science. In this context, this work aimed to present to 2nd year high school students in Redenção do Gurguéia in Piauí, Brazil, the use of experimental activities with low-cost materials through video classes, providing an innovative and aggregating experience in the teaching/learning process, in times of the Covid-19 pandemic. With that in mind it’s necessary to analyze the teaching through remote media in this pandemic period, to discuss the importance in developing alternative methodologies in teaching chemistry and to emphasize the use of experimental activities in teaching through low cost, easy access materials. Thus, realized the elaboration and application of questionnaire for levantaments data about the conceptions of the teachers and students then, video recordings of three low-cost experiments were made to help students in the Study of Thermodynamics and to analyze conceptions about the influence of experiments on teaching and learning. Faced with this the experimental activities recorded on video with low cost materials arises as an important alternative methodology to teach chemistry in this current period of remote classes, Therefore, verified that experimental activities recorded on videos with low-cost materials emerge as an important alternative methodology for teaching chemistry in this current scenario of remote chemistry classes, as it was observed that students are more interested in the subject, having a simpler view. to study chemistry as well as improve teaching-learning, making the chemistry lessons more interesting and fun.